2014
DOI: 10.1038/srep06235
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis, characterisation and in vivo study of a bioceramic for potential tissue regeneration applications

Abstract: Hydroxyapatite (HAP) is a biocompatible ceramic that is currently used in a number of current biomedical applications. Recently, nanometre scale forms of HAP have attracted considerable interest due to their close similarity to the inorganic mineral component of the bone matrix found in humans. In this study ultrafine nanometre scale HAP powders were prepared via a wet precipitation method under the influence of ultrasonic irradiation. The resulting powders were compacted and sintered to form a series of ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…17,18 For completeness, a brief procedural description is outlined as follows. The procedure begins by first adding a 40mL solution of 0.32 M calcium nitrate tetra-hydrate into a small glass beaker and then adjusting the solution pH to 9.0 using approximately 2.5ml of ammonium hydroxide.…”
Section: Preparation Of Nanometer Scale Hap Powdersmentioning
confidence: 99%
“…17,18 For completeness, a brief procedural description is outlined as follows. The procedure begins by first adding a 40mL solution of 0.32 M calcium nitrate tetra-hydrate into a small glass beaker and then adjusting the solution pH to 9.0 using approximately 2.5ml of ammonium hydroxide.…”
Section: Preparation Of Nanometer Scale Hap Powdersmentioning
confidence: 99%
“…Calcium phosphate (CaP) coating can be applied to a variety of substrate materials of varying sizes and shapes using a relatively straight forward technique known as chemical immersion [55,56]. Apart from convincing experimental results of a number of independent studies that indicate CaP coatings can significantly improve corrosion resistance [57][58][59], the coatings also have the advantages of being non-toxic, display good biocompatibility and have enhanced bioactivity properties with respect to bone cells and other body tissues [60]. Despite these many advantages, a number of studies have also shown a number of shortcomings such as poor coating adherence, surface cracking and effective control of the CaP phases formed during immersion [54].…”
Section: Controlled Degradation Via Chemical Immersion Treatmentmentioning
confidence: 99%
“…For many years, a variety of biologically compatible ceramics such as alumina, bioactive glasses, calcium phosphates and zirconia have been used in reconstructive and regenerative hard tissue procedures with varying degrees of success [1][2][3]. Importantly, any ceramic being considered for a biomedical application must be completely biologically compatible.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for bone tissue engineering applications it offers good osteoconductivity and osteoinductivity capabilities. While it's slow biodegradability in situ allows tissue regeneration and tissue replacement to take place [3,11,12]. These properties are of particular importance since bone continually undergoes cellular remodeling and as a result tissue is simultaneously deposited by osteoblasts cells and removed by osteoclasts cells [3,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation